2015
DOI: 10.1016/j.jcz.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Life history and ecological genetics of the colonial ascidian Botryllus schlosseri

Abstract: The colonial ascidian Botryllus schlosseri is a cosmopolitan, marine filter feeder, introduced as a laboratory research\ud organism in the 1950s. Currently, it is widely used in many laboratories to investigate a variety of biological questions.\ud Recently, it has become a species of concern, as it is an invasive species in many coastal environments. Here, we review\ud studies on the geographical distribution of the species, sexual and asexual reproduction in the field, tolerance to\ud temperature, salinity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…blue vs orange) 5,6 . The colors of the pigment cells in B. schlosseri are genetically determined 42,43 . Pigment cells, identified as CP8, circulate in the vasculature and are linked to the hematopoietic lineages by gene expression (Extended Data Fig.…”
Section: Methodsmentioning
confidence: 99%
“…blue vs orange) 5,6 . The colors of the pigment cells in B. schlosseri are genetically determined 42,43 . Pigment cells, identified as CP8, circulate in the vasculature and are linked to the hematopoietic lineages by gene expression (Extended Data Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, its responses to the presence of heavy metals were clearer and proportional to the concentration, especially after 24 and 48 h of exposure. Consequently, although various authors indicated B. schlosseri as a good bioindicator for ecotoxicological studies on organic xenobiotics [53,54], this study demonstrates the limits for such applications. Many studies were conducted on the toxicity of PAHs on marine organisms of commercial and ecological importance [5,55,56].…”
Section: Discussionmentioning
confidence: 55%
“…The difference in structure of granular inclusions in the vacuoles is probably attributable to the difference of the components in the granules. In botryllid ascidians, the colonies of the differently-colored strains have distinct structures of the pigment cell granules (Burighel et al 1983), and polychromatic colonies have several types of pigment cells characterized by different forms of granules in the vacuole (Hirose et al 1998, Cima et al 2015. Accordingly, the difference in the granular contents of the storage cells is probably the reason for the difference in coloration between P. confoederata (pinkish-brown) and T. democratica (transparent or blueish).…”
Section: Hemocyte Types and Their Possible Functionsmentioning
confidence: 99%